Essential Role of ATP Synthesized by Creatine Kinase in Contraction of -Toxin Permeabilized Preparations of Tonic Type Smooth Muscle - Tadayoshi Takeuchi; Muneyoshi Kitayama; Masahiko Kushida; Akikazu Fujita; Fumiaki Hata (Elsevier, 2003)
The role of ATP newly synthesized from ADP and phosphocreatine (PC) by creatine kinase (CK) in the contraction of tonic type smooth muscle, rat femoral artery was studied, since its necessity for phasic type smooth muscle was previously shown. In α-toxin-permeabilized preparations obtained from rat femoral artery, Ca2+ induced a tonic type contraction in the presence of ATP and PC. Omission of PC inhibited significantly the contraction. Treatment of the preparations with 2,4-dinitrofluorobenzene, an inhibitor of CK, also inhibited the contraction. In the presence of ADP and PC, Ca2+ also induced the contraction to a level comparable to that in the presence of ATP and PC. The extent of phosphorylated myosin light chain was fairly consistent with that of Ca2+-induced contraction under all experimental conditions planned above. These results suggest that ATP newly synthesized by CK essentially participates in the whole of the contraction in tonic type smooth muscle, although it participates only in a rapid phasic contraction in phasic type muscle as previously shown.